2012
DOI: 10.5588/ijtld.10.0565
|View full text |Cite
|
Sign up to set email alerts
|

Post-migration screening for active tuberculosis in Victoria, Australia

Abstract: Selective post-migration screening can achieve a high yield of notified TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
(9 reference statements)
0
6
0
1
Order By: Relevance
“…Alvarez et al surveyed screening practices in high migration, low incident countries in 2008 and found that on-entry screening was undertaken by Norway, Switzerland and the UK (out of a total of 13) and often aimed at migrant sub-populations -for example limiting screening to migrants from countries with higher estimated TB incidence, or to high risk populations, such as refugees or asylum seekers (16). Some countries utilise post-arrival screening programmes, for example as a required component of access to specific services, in holding centres (26) or as follow up to pre-entry screening (27), and these are often limited to specific high risk target populations or settings (17). Pre-entry screening programmes are now used by a number of countries.…”
Section: Effectiveness Of Active Tb Screeningmentioning
confidence: 99%
“…Alvarez et al surveyed screening practices in high migration, low incident countries in 2008 and found that on-entry screening was undertaken by Norway, Switzerland and the UK (out of a total of 13) and often aimed at migrant sub-populations -for example limiting screening to migrants from countries with higher estimated TB incidence, or to high risk populations, such as refugees or asylum seekers (16). Some countries utilise post-arrival screening programmes, for example as a required component of access to specific services, in holding centres (26) or as follow up to pre-entry screening (27), and these are often limited to specific high risk target populations or settings (17). Pre-entry screening programmes are now used by a number of countries.…”
Section: Effectiveness Of Active Tb Screeningmentioning
confidence: 99%
“…Linkage of records across databases has become an important tool for combining records that belong to the same entity across different data sources [ 8 , 9 , 16 20 ]. This activity consists of matching records in one database to records in another database, often a population registry, and creating a unique encoded identifier that is identical across the databases (henceforth called “record linkage”).…”
Section: Introductionmentioning
confidence: 99%
“…19 Such approaches have been demonstrated to be effective for active tuberculosis, however they would need to be developed and assessed for effectiveness in relation to the particular needs of LTBI management. 20 Screening policy may be applied to all immigrants, or could be limited to a subset (for instance, those from countries with a higher prevalence of tuberculosis infection, or those considered at higher personal risk, such as refugees and asylum seekers or immigrants with HIV infection). 21 Any such limitation in the scope of screening policy would need to be justified on clear objective grounds to ensure that arbitrary discrimination did not occur.…”
Section: Circumstances Of Screeningmentioning
confidence: 99%